Decolonising sambo : transculturation, fungibility and black and people of colour futurity - Tate, Shirley Anne (Critical mixed race studies., 2019)
This book decolonises 'sambo' as racialised knowledge, power, being and affect to unsettle its place in the history of 'mixed race' and racialised naming forged through settler colonialism which in its afterlife continues to haunt our contemporary period through national commemoration, cultural production and markets in contemptible collectibles.